Spatial price integration among selected bean markets in Malawi: A threshold autoregressive model approach - Mtumbuka, Wezzie S.; Mapemba, Lawrence; Maonga, Beston; Mwabumba, Mannex (International Food Policy Research Institute, 2014)
This research examines the extent of market integration among different bean markets across Malawi. Market integration is an indicator that efficiency exists within the flow of information between markets. The study focused on beans as they are a cheap source of protein affordable by the majority of rural smallholder farmers. Market price data for beans was obtained from the Ministry of Agriculture and Food Security and covered the period 1995 to 2011. The markets included in the study are Chitipa, Rumphi, Mzuzu, Lilongwe, Mitundu, Lizulu, Lunzu, Luchenza, and Bangula. Like prices of other agricultural crops, bean prices follow a general seasonal pattern, rising with increasing time since the last harvest and decreasing during the harvest period.